Unlocking novel opportunities: How online ideation platforms implicitly guide employees toward better ideas by spurring their desire to innovate - Tobias Kruft; Alexander Kock (Creativity and Innovation Management, 2021)
Employees' innovative behaviour becomes increasingly important for organizational success. Companies try to improve their innovation capabilities by supporting and motivating employees to show innovative behaviour. Particularly online ideation platforms become relevant because they create new opportunities for employees to be innovative. This paper investigates how exposure to online ideation platforms' unique capabilities stimulates intrinsic motivation toward innovative behaviour and ultimately the submission of high-quality ideas. Based on expectancy and channel expansion theories, we derive a framework with four intrinsic motivational forces that online ideation platforms can stimulate. A two-study approach empirically tests this framework. The first study uses a multilevel regression on a dataset of 1630 employees nested in 136 departments of a leading international science and technology company. The second study analyses how 279 employees of the same company, who submitted 678 ideas on the company's online ideation platform, continue to be motivated by the platform's inherent characteristics and capabilities and submit high-quality ideas. The results support the core argument that online ideation platforms stimulate certain desires motivating employees to engage in innovative behaviour and ultimately submit high-quality ideas. The detailed results offer several contributions to innovation management literature and beyond.
Keywords: 330; desires; innovative behaviour; motivation; online ideation platforms